2019
DOI: 10.1177/2329490619885891
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring in Business and Professional Communication: Case Study of a Multiyear Dynamic

Abstract: Mentoring of graduate students is essential to the professional development of business and professional communication (BPC) scholars; it also helps advance the field of BPC and its disciplinary identity. In this article, a professor and graduate student use a case-study approach incorporating historical/archival data collection and grounded in critical reflection to describe and characterize their own long-term, cross-institutional mentoring relationship. They analyze artifacts from their mentoring experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The idea of mentoring traces back to Homer's Odyssey, which includes a character named Mentor (goddess Athena in disguise), who helps Odysseus's son Telemachus find the strength (menos) and connections (napios) necessary to overcome the challenges (Rosselot-Merritt & Bloch, 2020).…”
Section: Mentor and Mentee Definition And Relationshipmentioning
confidence: 99%
See 2 more Smart Citations
“…The idea of mentoring traces back to Homer's Odyssey, which includes a character named Mentor (goddess Athena in disguise), who helps Odysseus's son Telemachus find the strength (menos) and connections (napios) necessary to overcome the challenges (Rosselot-Merritt & Bloch, 2020).…”
Section: Mentor and Mentee Definition And Relationshipmentioning
confidence: 99%
“…The development of a mentoring relationship depends on the perceptions and activities of both the mentor and mentee. If one or the other does not choose to engage actively, then the relationship will unlikely be as effective (Rosselot-Merritt & Bloch, 2020). Theoretical literature stresses the importance of two-way communication to make mentoring relationships work.…”
Section: Communication In the Mentormentee Relationshipmentioning
confidence: 99%
See 1 more Smart Citation
“…In an educational context, mentoring is a temporary collaborative relationship of two teachers based on the relationship between a more experienced teacher and a novice, or a beginner teacher. It is an essential relation where mentors use all the strategies that the communication style provides; it has his own dynamic and involves a constant learning process of mentor and mentee, constant adjusting and more of that it is not assimilated with career counselling process (Rosselot-Merrit & Bloch, 2019); it involves a special leaning environment. The studies done in 2015 by Vinales revealed that in learning environment and also in special education, the majority of mentors is predominantly female and the role that they played role as facilitator.…”
Section: Conceptual Analyses and Backgroundmentioning
confidence: 99%